Penanda Interogativa Ka pada Iklan Layanan Masyarakat Jepang: Studi Kasus pada Iklan Produksi AC Japan - Putri, Riyanda Daniati; Firmansyah, Dian Bayu; Hartati, Hartati (DBSMB, Vocational College of Universitas Gadjah Mada, 2023)
This research discusses the forms and functions of interrogative marker ka and defines its use in Japanese public service advertisements, which AC Japan distributes. The method that is used in this research is a descriptive qualitative study. The research data is sentences with interrogative marker ka, which is found in AC Japan advertisements distributed on Japanese television in the last five years (2017-2021). The theory of forms and functions of interrogative marker ka by Yokoyama (2013) was used in this research. The watch-note technique was used in this research to collect data that would be needed. The data were analyzed with formalist and functionalist approaches. After that, the data would be analyzed by aspects of speech that affect the forms and functions of interrogative marker ka. The result showed that the interrogative marker ka in AC Japan advertisements has a function to state common questions, rhetorical questions, conjectural questions, polar imperatives, and embedded questions. From these several functions, rhetorical questions are more widely used because advertising is an indirect communication medium, which still has to pay attention to the emphasis on the message to be conveyed.